The prevalence and incidence of fencing injuries and associated risk factors: A systematic review and meta-analysis - Wong, S. C. Y.; Chang, J. R.; Chan, L. L. Y.; Lee, M. S. H.; Grivas, T. B.; Samartzis, D.; Fu, S.-N.; Fong, H. H. K.; Wong, A. Y. L. (Clinical Journal of Sport Medicine, 2025)
Objective: To summarize the prevalence, incidence, and factors associated with fencing injuries among able-bodied (AFs) and wheelchair fencers (WFs).